Effects of crushed ice and wetted ice on hamstring flexibility - Larsen, C. C.; Troiano, J. M.; Ramirez, R. J.; Miller, M. G.; Holcomb, W. R. (The Journal of Strength and Conditioning Research, 2015)
Flexibility, which is the ability to move freely through a full range of motion (ROM), is desired to enhance the performance and decrease the likelihood of muscle injury. There are different techniques used to increase ROM and cryotherapy techniques to facilitation flexibility gains. However, the combination of stretching and type of cryotherapy agents are still confounding. The purpose was to determine which type of cryotherapy, crushed or wetted ice, would produce the greatest gains in hamstring ROM when followed by proprioceptive neuromuscular facilitation (PNF) stretching. Fifteen healthy subjects underwent 3 treatment conditions: crushed ice bag (crushed ice), wetted ice bag (wetted ice), and no ice bag (no ice). Subject's hamstring ROM was measured at baseline, then again after a 20-minute cryotherapy treatment session. Subjects were then stretched using a slow-reversal-hold-relax PNF technique followed by a final ROM measurement. A repeated measures analysis of variance showed significant differences between cryotherapy and measurement conditions. Post hoc testing indicated that no ice (75.49 ± 12.19° C) was significantly different from wetted ice (81.73 ± 10.34° C) and crushed ice (81.62 ± 13.19° C) at the end of the treatment session, and that no ice (85.27 ± 13.83° C) was significantly different than wetted ice (89.44 ± 11.31° C) and crushed ice (89.16 ± 13.78° C) after the stretching session. However, there were no differences between wetted ice and crushed ice. Results indicate that strength and conditioning specialists can increase ROM with both forms of ice in combination with PNF stretching more so than when using no ice at all.